Infiltration of M2 Tumor-Associated Macrophages in Oral Squamous Cell Carcinoma Correlates with Tumor Malignancy - Mori, Kazumasa (Molecular Diversity Preservation International (MDPI), 2011)
Tumor-associated macrophages (TAMs) are a major cellular component in the tumor microenvironment of many solid tumors. The functional competence of TAMs varies depending on the type of tumors and their respective microenvironments. The classically activated M1 macrophages exhibit antitumor functions, whereas the alternatively activated M2 macrophages exhibit protumor functions that contribute to tumor development and progression. Although TAMs have been detected in oral squamous cell carcinoma (OSCC), little is known about their phenotype. In the present study, we performed an immunohistochemical analysis to identify TAMs in surgically resected specimens from 50 patients with OSCC and evaluated the relationship between infiltrated TAMs and the pathological grade of OSCC. Positive staining for CD163, which has been used as a marker for M2 macrophages, was observed in OSCC specimens, and the percentages of CD163(+) cells were significantly increased based on the pathological grade. CD163(+) cells were detected in the tumor stroma in grade I tumors, whereas an increase in the CD163(+) cells in the tumor nest was observed in higher grades of tumors. Although infiltrated CD4(+) and CD8(+) T cells were detected in all pathological grades of OSCC, no correlation between the infiltrated T cells and the CD163(+) TAMs was observed. These results indicate that the infiltrated TAMs in OSCC have an M2 phenotype and that the M2 macrophages may participate in the development of OSCC.